2021
DOI: 10.3390/vaccines9091031
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of the Kinetics of Specific Antibodies to SARS-CoV-2 Infection and to Four SARS-CoV-2 Vaccines Available in Serbia, and Vaccine Effectiveness: A 3-Month Interim Report

Abstract: Real-life data on the performance of vaccines against SARS-CoV-2 are still limited. We here present the rates of detection and levels of antibodies specific for the SARS-CoV-2 spike protein RBD (receptor binding domain) elicited by four vaccines available in Serbia, including BNT-162b2 (BioNTech/Pfizer), BBIBP-CorV (Sinopharm), Gam-COVID-Vac (Gamaleya Research Institute) and ChAdOx1-S (AstraZeneca), compared with those after documented COVID-19, at 6 weeks and 3 months post first vaccine dose or post-infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
5
16
1
Order By: Relevance
“…However, this humoral response diminished progressively between the 90th to 180th day after the second dose, particularly in the NPI group, where lower anti-S-RBD IgG and NAbs were detected than those PI. The seroconverted proportion in the study was comparable but discretely lower than the results reported on phases 1 and 2 of the BBIBP-Corv-2 clinical trials [ 18 ] and other observational studies [ 19 , 20 , 21 ], although higher than that reported by Lijeskic [ 22 ]. However, we did not find a difference in the proportions of seroconverts according to age group, probably because most of our participants were adults under 50 years, and these differences in the humoral response are primarily observed in older patients.…”
Section: Discussionsupporting
confidence: 41%
“…However, this humoral response diminished progressively between the 90th to 180th day after the second dose, particularly in the NPI group, where lower anti-S-RBD IgG and NAbs were detected than those PI. The seroconverted proportion in the study was comparable but discretely lower than the results reported on phases 1 and 2 of the BBIBP-Corv-2 clinical trials [ 18 ] and other observational studies [ 19 , 20 , 21 ], although higher than that reported by Lijeskic [ 22 ]. However, we did not find a difference in the proportions of seroconverts according to age group, probably because most of our participants were adults under 50 years, and these differences in the humoral response are primarily observed in older patients.…”
Section: Discussionsupporting
confidence: 41%
“…Studies comparing immunogenicity of mRNA vaccines to that of BBIBP-CorV have generally reported lower seroconversion rates and antibody titers in the latter. Lijeskić et al [ 33 ] investigated three vaccines: BNT162b2, BBIBP-CorV, and Gam-COVID-Vac, and observed less potent immune responses in BBIBP-CorV as compared to the other two, while COVID-19 convalescents in this study demonstrated higher titers than BBIBP-CorV, but less than BNT162b2. Petrović et al [ 27 ] similarly reported lower seroconversion rates and antibody titers following BBIBP-CorV than either BNT162b2 or Gam-COVID-Vac.…”
Section: Resultsmentioning
confidence: 53%
“…Fu et al report 75% seroconversion rate using SARS-CoV-2 RBD ELISA [ 29 ], while Elgendy et al reveal 49% seroconversion, but have tested participants at Day 18 following BBIP-CorV vaccination [ 30 , 31 ]. Alqasseih et al report 85.7% seroconversion at 6 weeks post two-dose BBIBP-CorV vaccine schedule, using a qualitative immunoassay [ 32 ], while Lijeskić et al [ 33 ] have reported 81.7% seroconversion, 6 weeks post-vaccination, using a two-step sandwich enzyme immunoassay method for RBD anti-S antibodies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study, however, did find cellular response even with the Sinopharm vaccine. The immunogenicity study from Lijeskić et al reporting data from Serbia [ 49 ] did not find lower antibody response in older subjects, however, the sample size was small.…”
Section: Discussionmentioning
confidence: 99%